Inhibition of GSK3 attenuates the intracellular multiplication of burkholderia pseudomallei and modulates the inflammatory response in infected macrophages and A549 epithelial lung cells - Pramila Maniam; Aishah Farliani Shirat; Hasidah Mohd Sidek; Ghazally Ismail; Noor Embi (Universiti Kebangsaan Malaysia, 2013)
Burkholderia pseudomallei, the causative agent of melioidosis, is an intracellular pathogen capable of invading and multiplying in both phagocytic and non-phagocytic cells. Infection results in an inflammatory response involving production of both pro- and anti-inflammatory cytokines. The cellular mechanism regulating this response, believed to play an important role in the pathogenesis of meliodoisis, is not fully understood. In recent years, glycogen synthase kinase-3 (GSK3) has been shown to assume a pivotal role in regulating production of these cytokines. Bacterial infection of host cells activates Toll-like receptors (TLRs) and results in the phosphorylation of GSK3β through activation of the phosphoinositide 3-kinase (PI3K) pathway. In this study, we investigated the effects of GSK3 inhibition in regulating B. pseudomallei-induced inflammatory response in macrophages and A549 epithelial lung cells. Our results showed that infection of cells with B. pseudomallei resulted in the increase of anti-inflammatory cytokine, IL-10 and pro-inflammatory cytokine, TNF-α. Pre-treatment of infected cells with GSK3 inhibitors caused further increase in the level of IL-10 but a significant decrease in TNF-α. These changes corresponded with the detection of phosphorylated GSK3β in infected cells treated with LiCl; suggesting that modulation of inflammatory response in B. pseudomallei infection involves phosphorylation of GSK3β (Ser 9). This could explain our observations from the invasion assays that pre-treatment of B. pseudomallei-infected cells with GSK3 inhibitors resulted in decreased intracellular replication of bacteria within macrophages and A549 epithelial lung cells. In summary, our results demonstrate a regulatory function of GSK3 in the modulation of cytokine levels during B. pseudomallei infection.